The Analysis of Early Childhood Habits 0f Playing and Indoors Games at RA Wadas Kelir - Nur Hafidz; Siti Zubaedah; Zainal Arifin Ahmad; Perdana Pashela (UPI Kampus Cibiru, 2022)
Play and gamesfor children are activities done by children with joy and pleasure. Children's play and games are perform by children in early childhood educational institutions. Play and games become children’s habit in daily activities, either intentionally or accidentally. The study aims to explore the analysis of children's habits of indoor play and games at RA Wadas Kelir. Research methods are used with observation, in-depth interviews, and documentation. The data obtained is then analyzed with interactive techniques, namely reduction, presentation of data, and withdrawal of conclusions. The results of this research, analysis of children's habits of playing and indoor games at RA Wadas Kelir include (1) habits of children's signs of play and indoor games, (2) habits of children's routines of indoor play and games, (3) habits of child reward play and indoor games. From the data collected obtained that the analysis of children's habits of play and indoor games design based on the three stages can optimize the growth and development of children both physically and psychologically.